THE EFFECT OF DEMOGRAPHIC FACTORS, FINANCIAL LITERATURE, AND FINANCIAL ATTITUDES ON THE FINANCIAL WELL-BEING OF SAVINGS AND LOAN COOPERATIVE MEMBERS IN SUBANG DISTRICT - M. Ramdan Gumelar; Nurul Adzra Nabilah; Rianiva Laela Permana (STIESA Press, 2023)
This research aims to determine the influence of demographic factors, financial literacy, and financial attitudes on financial well-being, both partially and simultaneously. The data used in this research is primary data by distributing questionnaires in the form of a Google form. The method used in sampling was the probability sampling method with a simple random sampling technique and the number of samples in this study was 100 respondents who were members of cooperatives in Subang Regency. The data was processed using data quality testing methods, classical assumption testing, multiple regression analysis, and hypothesis testing. The results of the research show that partially the demographic factor variables have a negative effect on financial well-being, while the financial literacy and financial attitude variables have a positive effect on financial well-being. Simultaneously, the results of this research show that demographic factors, financial literacy and financial attitudes have a positive effect on financial well-being.